PERAN DISIPLIN KERJA, KOMPENSASI, DAN STRES KERJA TERHADAP KINERJA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PUSKESMAS PANJI KABUPATEN SITUBONDO - Fitria, Ulfi Nurul; Arief, Mohammad Yahya; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Humans are an important and dominant factor in carrying out work or activities in an organization, because humans become actors, determining the realization of organizational goals. The aim of this research is to analyze and test the influence of work discipline, compensation and work stress on performance through work motivation. This research is quantitative research. The population in this study were ASN employees at the Panji Community Health Center. The sampling technique uses saturated sampling. Data analysis and hypothesis testing in this research used the â‚‹ Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that work discipline has no significant effect on work motivation, compensation has no significant effect on work motivation, work stress has a significant effect on work motivation, work discipline has no significant effect on performance, compensation has a significant positive effect. on performance, work stress has no significant effect on performance, work motivation has a significant effect on performance. The results of the indirect influence hypothesis test show that the variable Work Discipline on Performance through Work Motivation has a positive but not significant effect, Compensation on Performance through Work Motivation has a positive but not significant effect, Work Stress on Performance through Work Motivation has a significant positive effect.